Sequence analysis of 139 kb in Xp22.1 containing spermine synthase and the 5' region of PEX. - Grieff, M; Whyte, M; Thakker, R; Mazzarella, R (1997)
Human Xp22.1 contains genes involved in mineral balance that are implicated in X-linked hypophosphatemia (XLH) in humans, its murine homologue (Hyp), and another distinct murine hypophosphatemic disorder (Gy). In XLH, a gene, PEX, has been found to be mutated in up to 83% of patients but the sequences of the promoter and 5' end have not been characterized. To further the understanding of this genomic region, 139,454 bp in Xp22.1 have been sequenced. Our analysis confirms the three most 5' published exons of PEX and extends through a putative PEX promoter region. The 5' untranslated sequence of PEX and the mouse and rat equivalents are very highly homologous, implying a conserved functional significance. In addition, we mapped and analyzed another gene 5' of PEX, spermine synthase (SpS), which encodes a ubiquitous enzyme of polyamine metabolism that may contribute to the pathophysiology of Gy. SpS consists of 11 exons spread over 54 kb. The definition of the locations of SpS and the putative promoter region of PEX will facilitate functional analysis of these genes.